2009
DOI: 10.1002/adfm.200801313
|View full text |Cite
|
Sign up to set email alerts
|

Signal‐On Electrochemiluminescence Biosensors Based on CdS–Carbon Nanotube Nanocomposite for the Sensitive Detection of Choline and Acetylcholine

Abstract: This work describes for the first time signal‐on electrochemiluminescence (ECL) enzyme biosensors based on cadmium sulfide nanocrystals (CdS NCs) formed in situ on the surface of multi‐walled carbon nanotubes (MWCNTs). The MWCNT–CdS can react with H2O2 to generate strong and stable ECL emission in neutral solution. Compared with pure CdS NCs, the MWCNT–CdS can enhance the ECL intensity by 5.3‐fold and move the onset ECL potential more positively for about 400 mV, which reduces H2O2 decomposition at the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
136
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(139 citation statements)
references
References 36 publications
2
136
1
Order By: Relevance
“…Recently, Xu et al synthesized the multi-walled carbon nanotubes-CdS nanocomposite by using electrochemical synthesis, and it showed sensitive ECL responses compared with that of the MWCNT-CdS composite obtained under simple ultrasonic mixing [11]. Thus it provides an idea for us to synthesize chromium-loaded ECL nanoprobe via in-situ system, which were expected to amplify the ECL signal of nanoprobes and improve the detection sensitivity.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, Xu et al synthesized the multi-walled carbon nanotubes-CdS nanocomposite by using electrochemical synthesis, and it showed sensitive ECL responses compared with that of the MWCNT-CdS composite obtained under simple ultrasonic mixing [11]. Thus it provides an idea for us to synthesize chromium-loaded ECL nanoprobe via in-situ system, which were expected to amplify the ECL signal of nanoprobes and improve the detection sensitivity.…”
Section: Introductionmentioning
confidence: 93%
“…Thus, finding a way to obtain high ECL efficiency of NCs for bioanalysis is the constant driving force of this area. Many previous works have demonstrated that ECL emissions of NCs are highly dependent on their surface states, which can be changed by coupling with other nonmaterial or doping some metal ions [10][11][12][13][14][15][16][17]. Deng et al and Wang et al reported that the doping of Mn 2+ or Eu 3+ ions in the CdS NCs surface alters the surface of CdS NCs and builds a new surface state-Mn 2+ or Eu 3+ complex, also produces a maximum of 4-fold enhancement in ECL intensity [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Upon the understanding of ECL mechanisms and the development of multitudinous coreactants, many new ECL systems of quantum dots (QDs) have been proposed by coreactant enhancing [2,3] or signal quenching [4]. However, the overwhelming used QDs ECL emitters were focused on II-VI QDs, which were of great biotoxicity and suffered instability during storage even at 4 8C.…”
Section: Doi: 101002/elan201100379mentioning
confidence: 99%
“…Since the first work on the ECL of silicon QDs was reported in 2002 , the ECL phenomena of CdS (Ding et al, 2006;Jie et al, 2007;Wang et al, 2009), CdSe (Jiang and Ju, 2007;Huang and Zhu, 2009), and CdTe (Liu and Ju, 2008) in the presence of different co-reactants such as oxygen, hydrogen peroxide or peroxydisulfate have been used for the development of ECL biosensors. Herein, the mercaptopropionic acid (MPA)-capped CdS quantum dots were firstly immobilized on carbon nanotubes modified electrode via a layer-by-layer method.…”
Section: Introductionmentioning
confidence: 99%